Analisis Kinerja Keuangan PT. Perusahaan Listrik Negara (Persero) Periode 2020-2024 - Wulandari, Sri; Anwar, Anwar; Amalia Hamka, Rezky; Ichwan Musa, Muhammad; Nurman, Nurman (BADAN PENERBIT STIEPARI PRESS, 2025)
Understanding customer behavior is a key element in creating an enjoyable shopping experience and maintaining customer satisfaction and loyalty. In the digital age, customers expect a seamless shopping experience both in physical stores and through online platforms. This study aims to analyze the influence of channel integration, service quality, and brand image on customer satisfaction and its implications for loyalty. The survey was conducted on 125 active Sephora customers in Jakarta who have made purchases through online and offline channels at least once a year. The results show that all three variables—channel integration, service, and brand image—have a significant effect on customer satisfaction levels. Satisfied customers are more likely to show loyalty through repeat purchases and recommendations to others. A consistent and convenient shopping experience across multiple channels is proven to strengthen the long-term relationship between customers and brands. These findings emphasize the importance of companies in designing marketing strategies that prioritize channel integration and quality service as the main foundation in building sustainable customer loyalty. This research makes a practical contribution to the development of retail business strategies based on customer experience, as well as a reference for companies in improving competitiveness through a holistic approach to customer satisfaction and loyalty.